2020
DOI: 10.3390/ijms21051649
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin in Animal Cognition and Behavior

Abstract: Serotonin (5-hydroxytryptamine, 5-HT) is acknowledged as a major neuromodulator of nervous systems in both invertebrates and vertebrates. It has been proposed for several decades that it impacts animal cognition and behavior. In spite of a completely distinct organization of the 5-HT systems across the animal kingdom, several lines of evidence suggest that the influences of 5-HT on behavior and cognition are evolutionary conserved. In this review, we have selected some behaviors classically evoked when address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(124 citation statements)
references
References 213 publications
2
111
0
Order By: Relevance
“…The role of the serotonergic (5-HT) system is well known to be an enigma (Jacobs and Fornal, 1995 ). 5-HT modulates animal cognition and behavior, including motor function, in a complex manner (for review Bacqué-Cazenave et al, 2020 ). Historically, the interest toward the study of 5-HT modulation of locomotor circuits followed the pioneering observations in Paris by Viala and Buser ( 1969 ), who showed that systemic injection of the 5-HT precursor 5-hydroxytryptophan (5-HTP) evoked fictive locomotor activity in rabbits (Viala and Buser, 1969 , 1971 ; see “5-HT Precursors” section).…”
Section: Introductionmentioning
confidence: 99%
“…The role of the serotonergic (5-HT) system is well known to be an enigma (Jacobs and Fornal, 1995 ). 5-HT modulates animal cognition and behavior, including motor function, in a complex manner (for review Bacqué-Cazenave et al, 2020 ). Historically, the interest toward the study of 5-HT modulation of locomotor circuits followed the pioneering observations in Paris by Viala and Buser ( 1969 ), who showed that systemic injection of the 5-HT precursor 5-hydroxytryptophan (5-HTP) evoked fictive locomotor activity in rabbits (Viala and Buser, 1969 , 1971 ; see “5-HT Precursors” section).…”
Section: Introductionmentioning
confidence: 99%
“…It participates in a number of important physiological functions [81,82]. The participation of the serotonin system in animal cognition and behavior, in learning and memory attracts increasing attention [28,[83][84][85]. Therefore, the deregulation of the serotonergic system causes the pathogenesis of many psychiatric and neurological disorders [84,86].…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of techniques for reducing the level of 5-HT. These are the use of 5-HT transporter blockers [85,90,94,95] and application of technologies associated with the exposure to 5-HT receptors [85,90,96,97]. Tryptophan hydroxylase, an enzyme that limits the rate of 5-HT synthesis, which regulates the activity of 5-HT in the brain, plays an important role [97][98][99][100][101].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5-HT regulates diverse brain functions such as autonomic nervous system reactivity, sleep cycles, and appetite [246,247]. Furthermore, 5-HT has a role in regulating various emotional behaviors such as anxiety, aggression, and affiliative behaviors [248]. Serotonergic projections originating from the brain stem raphe nuclei innervate nearly every part of the forebrain including the HYP, AMY, prefrontal cortex, and hippocampus where the 5-HT effects are mediated via 15 different 5-HT receptors [249].…”
Section: Hormonal Neuroprotection Via Recruitment Of 5-htmentioning
confidence: 99%